Everything you need to know about teen suicide - Schleifer, Jay. (New York City, N.Y. : Rosen Pub. Group, 1988)
Examines reasons why young people kill themselves, how to recognize when friends are in such trouble, and how to help potential suicide victims.
Includes index.
Bibliography: p. 61-62.
Keywords: Teenagers -- Suicidal behavior -- United States -- Juvenile literature; Suicide -- United States -- Prevention -- Juvenile literature; Suicide